Ficus virens Aiton var. dispersa (Moraceae): a new record for India - Nair, Sreehari Sivan; Bachan, Kandarumadathil Hyder Amitha; Ebin, Padiyara Joy (Biodiversity: Research and Conservation, 2021)
An interesting specimen of Ficus L. was collected from the Idukki district of Kerala. Based on detailed examination with protologues, literatures and type specimens, the plant was identified as Ficus virens Aiton var. dispersa Chantaras. This is the first report on the occurrence of this taxon in India. A detailed description, photographs, illustrations, comparison with allied taxa and identification key are provided.